1976
DOI: 10.1113/jphysiol.1976.sp011636
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the influence of membrane potential and metabolic poisoning with azide on the sodium pump in skeletal muscle.

Abstract: 1. Activation of the Na pump in muscle by the external K concentration, [K]O, is independent of the membrane potential (Em) as shown by experiments in which Em was either stabilized during variation of [K]O or varied by application of azide at constant or zero [K]O. 2. Application of azide to Na‐enriched muscles causes a transient increase in 22Na efflux which occurs either in the presence or in the absence of external K. 3. The increased 22Na efflux induced by azide is abolished by addition of ouabain and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
1

Year Published

1982
1982
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
2
13
1
Order By: Relevance
“…Before the recent investigation of the influence of voltage on different partial reactions, the overall effect of electrogenicity was observed in terms of voltage-current dependence of the Na,K pump. The influence of membrane voltage on the pumping current has been determined in nerve membranes (Hodgin & Keynes, 1955;Thomas, 1972;Rakowski, Gadsby & DeWeer, 1989), heart (Eisner & Lederer, 1980;Glitsch, 1982), muscle (Beaug6 & Sjodin, 1976;Lederer & Nelson, 1984), red blood cells (Milanick & Hoffman, 1986) and in vesicles containing reconstituted Na,K pump (Goldschleger et al, 1987;Apell & Bersch, 1988). Of particular interest is the question: in which step (or steps) of the transport cycle is charge translocated?…”
mentioning
confidence: 99%
“…Before the recent investigation of the influence of voltage on different partial reactions, the overall effect of electrogenicity was observed in terms of voltage-current dependence of the Na,K pump. The influence of membrane voltage on the pumping current has been determined in nerve membranes (Hodgin & Keynes, 1955;Thomas, 1972;Rakowski, Gadsby & DeWeer, 1989), heart (Eisner & Lederer, 1980;Glitsch, 1982), muscle (Beaug6 & Sjodin, 1976;Lederer & Nelson, 1984), red blood cells (Milanick & Hoffman, 1986) and in vesicles containing reconstituted Na,K pump (Goldschleger et al, 1987;Apell & Bersch, 1988). Of particular interest is the question: in which step (or steps) of the transport cycle is charge translocated?…”
mentioning
confidence: 99%
“…On the other hand, the Na+-pump activity appears to be independent of membrane potential in a variety of tissues including squid giant axon (HODGKIN and KEYNES, 1955;BRINLEY and MULLINS, 1974), Anisodoris giant neurone (MARMOR, 1971), human red blood cells (COTTERRELL and WHITTAM,1971), frog skeletal muscle (BEAUGE and SJODIN, 1976), and sheep Purkinje fiber (EISNER and LEDERER, 1980). TAHARA et al (1973) suggested that the activity of the Nat-pump is directly dependent upon membrane potential in frog skeletal muscle.…”
mentioning
confidence: 99%
“…Brinley and Mullins (1974) have reported that in squid axons the Na,Kpump activity is independent of the membrane potential. As shown by Beaug6 et al (1975) Beaug6 and Sjodin (1976), the activation of the Na,K-pump in frog skeletal muscles by a rise of external K concentration is independent of external K-induced change in the membrane potential. Lederer and Nelson (1984) have also reported that the Na transport mediated by the Na,K-pump is not voltage-dependent in barnacle muscles.…”
Section: Discussionmentioning
confidence: 93%